Evaluating ICT Project Sustainability Using Business Intelligence and Fuzzy AHP - Mogale, Gwendoline Moshishi; Esiefarienrhe, Bukohwo Michael (Journal of Information System and Informatics, 2025)
This study explores persistent sustainability challenges in ICT projects despite the widespread availability of project management tools. A mixed-method approach combining inspections, observations, and a structured questionnaire was used to evaluate the six key framework attributes drawn from existing literature. The rating response from the experienced and professional ICT projects field experts, which were based on a three-point scale, were further analyzed using Microsoft’s MicroStrategy dashboard (BI). The rating outcomes predominantly revealed the outcome as follows: Value Proposition (100% - agree), Strategy (92% - agree), Governance (92% - agree), Environmental Risk Assessment (50% disagree, but 42% agree), Time Management (83% - neutral, but 17% agreed), and Resource Capacity (92% - neutral, but 8% agreed). Subsequently, Fuzzy Analytic Hierarchy Process (F-AHP) model was applied to determine the relative priority of each attribute/factor. The usage of MS MicroStrategy dashboards (BI) enabled transparent visualization of expert ratings, while F-AHP provided structured prioritization and consistency validation through Saaty’s 10% rule. The integration of BI and F-AHP resulted in a study’s VSGETR framework which offers a scalable, data-driven model tailored to public sector governance, bridging strategic objectives with operational execution. Findings in this study suggest that embedding this framework into project policies and evaluation checklists can significantly improve sustainability oversight and resource monitoring in ICT initiatives.